The Effect Of Financial Distress, Profit Management And Leverage On Tax Aggressiveness - Vinenda Juane Takasanakeng (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this study was to determine the positive effect of Financial Distress, Earnings Management and Leverage on Tax Aggressiveness. The data analysis method used is Multiple Linear Regression. The results of the partial test (t-test) that has been done, it was found that Financial Distress, Earnings Management and Leverage have no effect on tax aggressiveness with a significance value of 0.422, 0.634 and 0.169. The implication of this research is to add insight that difficult conditions are not always an indication of tax aggressiveness and this research as a reference to minimize tax aggressiveness. The population in this study is the Financial Statements of the Telecommunications sector listed on the Indonesia Stock Exchange (IDX) in 2017-2021 with a sample selection using the Purposive Sampling technique with a total of 7 (seven) samples.